Transcription and chromatin regulation by TAF4b during cellular quiescence of developing prospermatogonia - Gura, Megan A.; Bartholomew, Myles A.; Abt, Kimberly M.; Relovská, Soňa; Seymour, Kimberly A.; Freiman, Richard N. (Frontiers in Cell and Developmental Biology, 2023)
Prospermatogonia (ProSpg) link the embryonic development of male primordial germ cells to the healthy establishment of postnatal spermatogonia and spermatogonial stem cells. While these spermatogenic precursor cells undergo the characteristic transitions of cycling and quiescence, the transcriptional events underlying these developmental hallmarks remain unknown. Here, we investigated the expression and function of TBP-associated factor 4b (Taf4b) in the timely development of quiescent mouse ProSpg using an integration of gene expression profiling and chromatin mapping. We find that Taf4b mRNA expression is elevated during the transition of mitotic-to-quiescent ProSpg and Taf4b-deficient ProSpg are delayed in their entry into quiescence.Gene ontology, protein network analysis, and chromatin mapping demonstrate that TAF4b is a direct and indirect regulator of chromatin and cell cycle-related gene expression programs during ProSpg quiescence. Further validation of these cell cycle mRNA changes due to the loss of TAF4b was accomplished via immunostaining for proliferating cell nuclear antigen (PCNA). Together, these data indicate that TAF4b is a key transcriptional regulator of the chromatin and quiescent state of the developing mammalian spermatogenic precursor lineage.